Diagnostic value of three-dimensional magnetic resonance imaging of inner ear after intratympanic gadolinium injection, and clinical application of magnetic resonance imaging scoring system in patients with delayed endolymphatic hydrops. Issue 1 (January 2014) - Gu, X; Fang, Z-M; Liu, Y; Lin, S-L; Han, B; Zhang, R; Chen, X
Abstract Objective: Three-dimensional fluid-attenuated inversion recovery magnetic resonance imaging of the inner ear after intratympanic injection of gadolinium, together with magnetic resonance imaging scoring of the perilymphatic space, were used to investigate the positive identification rate of hydrops and determine the technique's diagnostic value for delayed endolymphatic hydrops. Methods: Twenty-five patients with delayed endolymphatic hydrops underwent pure tone audiometry, bithermal caloric testing, vestibular-evoked myogenic potential testing and three-dimensional magnetic resonance imaging of the inner ear after bilateral intratympanic injection of gadolinium. The perilymphatic space of the scanned images was analysed to investigate the positive identification rate of endolymphatic hydrops. Results: According to the magnetic resonance imaging scoring of the perilymphatic space and the diagnostic standard, 84 per cent of the patients examined had endolymphatic hydrops. In comparison, the positive identification rates for vestibular-evoked myogenic potential and bithermal caloric testing were 52 per cent and 72 per cent respectively. Conclusion: Three-dimensional magnetic resonance imaging after intratympanic injection of gadolinium is valuable in the diagnosis of delayed endolymphatic hydrops and its classification. The perilymphatic space scoring system improved the diagnostic accuracy of magnetic resonance imaging.